Biodiversity assessment of the Lower Mekong Basin: A new species of Corvospongilla (Porifera: Spongillina: Spongillidae) from Thailand - Ruengsawang, Nisit; Sangpradub, Narumon; Hanjavanit, Chutima; Manconi, Renata (Zootaxa, 2012)
Only six species (four genera, one family) of freshwater sponges are known until now from Thailand. A first record of thegenus Corvospongilla Annandale, 1911 with the description of a new species is here reported from the Pong River in the LowerMekong Basin. The taxonomic status of Corvospongilla siamensis nov. sp. is discussed in comparison to the 18 speciesassigned to the genus. The new species is characterised by i) alveolate, paucispicular skeletal network with scanty spongin,thick ascending tracts towards the sponge surface to support conules; ii) skeleton of stout microspined strongyles, andextremely rare, abruptly pointed oxeas usually with a few tubercles, plus micropseudobirotules with smooth shaft; iii) gem-mules belonging to a single gemmular morph, typically sessile; iv) gemmular cage notably stout, of tangentially arrangedstrongyles of variable length from tubercled to spiny; v) gemmular theca with abundant laminar compact spongin, lackingpneumatic layer, armed by short, tubercled to spiny strongyles tangentially embedded; vi) larvae armed by spiny oxeas. Corvo-spongilla siamensis nov. sp. differs from all the other known species of the genus in its unique combination of diagnostic traits,particularly a) acanthostrongyles (megascleres), b) gemmuloscleres, both in the cage and in the theca, as strongyles showing the tendency towards ring-shape and button-like shape, and c) larval spiny oxeas.